Histopathology of Noncutaneous Small Biopsy Specimens: The Diagnostic Value of Deeper Sections - Ayesha Imtiaz Malik, Mariam Riaz, Sara Ali Jadoon, Abdul Haseeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to determine the incidence of deeper sections and the diagnostic value of these sections in non-cutaneous small biopsy specimens taken at a hospital. Study Design: Cross-sectional study Place and Duration: DHQ Teaching Hospital, Abbottabad; Jan 2022-Jun 2022. Methods: 76 patients aged 18-48 were presented in this study. Patients admitted to the oral and maxillofacial department who underwent deeper sections were included. After obtaining informed and written consent, complete demographic information was obtained. In all cases, the sites of organs and levels for seep sections were recorded. Categorical variables were assessed using mean, standard deviation, frequency, and percentages. Results: Researchers found that majority of the deeper sections, 40 (52.6%) cases were from the cervix, followed by stomach, endometrium, and colorectal. Level 4 was the most commonly performed deeper section among 18 (23.7%) cases. Even though a diagnosis could be made from the first slide, deeper levels were examined in 41 (53.9%) cases to explore other histological characteristics. This was to either increase the reliability of the diagnosis made from the first slide or to confirm that diagnosis. Of these 41 instances, 14 (34.1%) revealed the same histological characteristics in deeper sections, whereas 27 (65.9%) revealed new pathological abnormalities. Conclusion: A definitive diagnosis often has to be based on a deeper section. Therefore, regardless of the lesion size, it is advised that deeper areas be performed on samples that cannot be reliably identified on normal levels. This procedure should be standardized worldwide. Keywords: Deeper Sections, Histopathology, Biopsy, Non-cutaneous